2021
DOI: 10.3390/foods10071532
|View full text |Cite
|
Sign up to set email alerts
|

The High Content of Quercetin and Catechin in Airen Grape Juice Supports Its Application in Functional Food Production

Abstract: Ensuring healthy lives and well-being constitutes one of the Sustainable Development Goals of the UN 2030 agenda. Consequently, research into how natural products may promote health is essential for the new generation of nutraceuticals and functional foods that are in high demand today. Grape juice is a natural foodstuff composed of water, sugars, minerals, vitamins and a wide array of polyphenols. Polyphenols are bioactive compounds of great interest due to their antioxidant properties and benefits to health,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 87 publications
0
18
0
Order By: Relevance
“…Grape juices consist of water (81%–86%) and a high concentration of sugars (glucose and fructose), with high acidity owing to the existence of organic acids that balance the sweet and sour tastes. They present small amounts of minerals, vitamins, and other phenolic aromatic compounds that provide sensory characteristics of grape juices (color, taste, and flavor) (Cosme et al., 2018 ; Dutra et al., 2021 ; García‐Martínez et al., 2021 ). Among the phenolic compounds found in grape juice are flavonols (kaempferol, quercetin, and myricetin), flavanols (catechin, epicatechin, and procyanidins), anthocyanins (malvidin, cyanidin, delphinidin, petunidin, peonidin, and pelargonidin), phenolic acids, and the stilbene resveratrol (Burin et al., 2010 ; Lima et al., 2014 ; Nadeem et al., 2018 ; O’Byrne et al., 2002 ; Xia et al., 2010 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grape juices consist of water (81%–86%) and a high concentration of sugars (glucose and fructose), with high acidity owing to the existence of organic acids that balance the sweet and sour tastes. They present small amounts of minerals, vitamins, and other phenolic aromatic compounds that provide sensory characteristics of grape juices (color, taste, and flavor) (Cosme et al., 2018 ; Dutra et al., 2021 ; García‐Martínez et al., 2021 ). Among the phenolic compounds found in grape juice are flavonols (kaempferol, quercetin, and myricetin), flavanols (catechin, epicatechin, and procyanidins), anthocyanins (malvidin, cyanidin, delphinidin, petunidin, peonidin, and pelargonidin), phenolic acids, and the stilbene resveratrol (Burin et al., 2010 ; Lima et al., 2014 ; Nadeem et al., 2018 ; O’Byrne et al., 2002 ; Xia et al., 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consumption of grape juice has positive health advantages due to effective antioxidant, anticarcinogenic, antibacterial, antidiabetic, antiaging, and anti‐inflammatory activities as well as cardioprotective, hepatoprotective, and neuroprotective effects (Nadeem et al., 2018 ; Wu et al., 2021 ), which develop endothelial function, increasing the antioxidant capacity of serum and low‐density lipoproteins, minimizing native plasma protein oxidation, and reducing platelet aggregation (Burin et al., 2010 ; Dávalos et al., 2005 ). Moreover, studies have shown the beneficial effects of resveratrol and quercetin in the treatment of cancer and cardiovascular diseases (García‐Martínez et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some other flavonoids and genistein increase the HDL (high-density lipoprotein) and decrease the BMI (body mass index). Naringin and berberine reduce the hypercholesterolemic level, decrease the blood lipid and quercetin molecules, and increase the blood HDL [ 134 , 135 ]. Alkaloid with antiobesity property isolated, synephrine from Citrus aurantium , nuciferine from Nelumbo nucifera , piperine and piperlongumine from Piper nigrum .…”
Section: Therapeutic Application Of Phytochemicals In Obesitymentioning
confidence: 99%
“…The United States, Spain, China, Italy, France, Turkey, and Chile are the top producers of grape juice ( 41 ). Grape juice contains water, high concentration of sugars and organic acids ( 42 , 44 , 45 ), and minerals, phenolic compounds, and other nutrients such as vitamins, proteins, fatty acids, and amino acids ( 46 , 47 ). Carbohydrates are found in the form of fructose and glucose ( 48 ).…”
Section: Contribution Of Grape Juice To Isotonic Drinksmentioning
confidence: 99%